Upaya Meningkatkan Hasil Belajar IPAS Materi Wujud Zat dan Perubahannya melalui Media Video dan Benda Konkret - Wulandari, Diana Rizki Avita; Widiyatmoko, Wahyu (FONDATIA, 2024)
The purpose of this study is to enhance the learning outcomes of class IV SD Muhammadiyah 4 Surakarta students studying the natural and social sciences. Concrete objects and video media are the research materials used in "The Form of Substances and Their Changes." This study is part of a class action. Two cycles of this classroom action study were conducted. In this study, sixteen fourth-graders from SD Muhammadiyah 4 Surakarta participated. The model utilized in this study is comprised of four stages: preparation, execution, monitoring, and analysis. Techniques for data reduction, presentation, and conclusion analysis are used in this study. The results of cycle I showed that ten students (62%) achieved completion and six students (38%) did not achieve completion. With an average score of 74.4 for Cycle I, the students' average score remained below the school's minimum completion criterion of 75. According to the second cycle's outcomes, 16 students—or 100%—had finished the course. Furthermore, during cycle II, the students' average score rose to 87.5, indicating that they had surpassed the school's minimum completion requirements of 75. The study's findings demonstrate how using video content with tangible things might enhance students' learning outcomes about forms of matter and changes in matter.